A Worldly Kingdom of Heaven in T. C. Chao’s Early Theology - ZHA, Changping (Journal of Research for Christianity in China (JRCC), 2025)
This paper discusses the conception of an ideal world present in T.C. Chao’s (Tsu Chen Chao) (1888-1979) early theological works, based mainly on the text Jesus’ Philosophy of Life (or, A New Interpretation of the Sermon on the Mount, written in late 1925). It concludes by pointing out that Chao’s view of a kingdom of heaven that ultimately eradicates the otherworld and does not transcend this world unconsciously echoes the Anti-Christian Movement within Chinese churches during the same period. This is, indeed, a tragedy in the development of T. C. Chao’s personal theological thought in the 1920s and 1930s.
Keywords: Personality, T. C. Chao, Theology, Worldly Kingdom of Heaven